Mortality in Antinuclear Antibody-Positive Patients with and Without Rheumatologic Immune-Related Disorders: A Large-Scale Population-Based Study - Uria Shani; Paula David; Ilana Balassiano Strosberg; Ohad Regev; Mohamad Yihia; Niv Ben-Shabat; Dennis McGonagle; Orly Weinstein; Howard Amital; Abdulla Watad (Medicina)
Background & Objectives: To explore the potential association between positive ANA serology and all-cause mortality in a large cohort of patients, including those with and without rheumatological conditions and other immune-related diseases. Material and Methods: A retrospective cohort study analyzed all-cause mortality among 205,862 patients from Clalit Health Services (CHS), Israel’s largest health maintenance organization (HMO). We compared patients aged 18 and older with positive ANA serology (n = 102,931) to an equal number of ANA-negative controls (n = 102,931). Multivariable Cox regression models were used to assess hazard ratios (HR) for mortality, adjusting for demographic and clinical factors. Results: ANA positivity was strongly associated with increased mortality (adjusted HR [aHR] 4.62; 95% CI 4.5–4.7, p < 0.001). Significant predictors of mortality included male gender (39.2% vs. 24.4%, p < 0.001), older age at testing (72.4 ± 13.0 vs. 50.1 ± 17.3 years, p < 0.001), and Jewish ethnicity (89.6% vs. 83.2%, p < 0.001). Certain ANA patterns, such as mitochondrial (and dense fine speckled (DFS-AC2)), were highly predictive of mortality, with aHRs of 36.14 (95% CI 29.78–43.85) and 29.77 (95% CI 26.58–33.34), respectively. ANA-positive patients with comorbid rheumatological immune-related disorders (RIRDs) demonstrated a higher survival rate compared to those without such a condition (aHR 0.9, 95% CI 0.86–0.95, p < 0.001). This finding remained significant after adjusting for several parameters, including age. Conclusions: ANA positivity is associated with increased all-cause mortality, particularly in individuals without rheumatologic disorders, after adjusting for confounders such as age. This may indicate occult malignancies, cardiovascular pathology, or chronic inflammatory states, necessitating more vigilant surveillance